Silver alloy target material and preparation method and application thereof
By adding Ce, Al-Cu alloy and Mn-Cu alloy to silver, combined with forging and rolling heat treatment, the microstructure morphology is controlled, the problem of the silver film being easily oxidized and sulfurized in the air is solved, and the silver alloy target material is realized. Highly effective anti-sulfurization and anti-oxidation properties, and improves its hardness and processability.
Patent Information
- Application Number
- CN202411260186.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing silver films are prone to oxidation and vulcanization in the air, resulting in the loss of its low resistance and high reflectivity characteristics, affecting the reliability of the device, and there is still room for improvement in its anti-vulcanization, oxidation and processing performance.
By adding Ce, Al-Cu alloy and Mn-Cu alloy to silver, combined with forging and rolling heat treatment, the microstructure morphology is controlled, the anti-sulfidation and anti-oxidation properties of the silver alloy target are improved, and its hardness and processability are improved. performance.
Without reducing the reflectivity, the anti-sulfide and anti-oxidation properties of the silver alloy target are greatly improved, its hardness and processing performance are improved, and the time for blackening, sulfide and oxidation is prolonged.
Smart Images

Figure CN119307770A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of target materials, and in particular relates to a silver alloy target material and a preparation method and application thereof. Background Art
[0002] Silver is often used as electrodes and reflective films in flat panel displays and optical recording due to its high reflectivity, high thermal conductivity, low resistance and low extinction coefficient. Pure silver has poor resistance to oxidation and sulfidation, mainly because silver easily reacts with O2 and H2S in the air when exposed to air to form oxide film and Ag2S, causing the silver film to lose its low resistance and high reflectivity characteristics, seriously affecting device reliability.
[0003] The anti-sulfurization and oxidation properties of silver alloy targets and their films all depend on the selection of their alloying components and the target's own microstructures such as grain size, crystal orientation and density. Therefore, improving the oxidation and sulfidation resistance of silver films by alloying and regulating the composition of the microstructure is an effective development method, and relevant researchers have already carried out a lot of work on this, but its anti-sulfurization and oxidation resistance, as well as processing performance, have a lot of room for improvement.
[0004] Therefore, there is an urgent need to develop a new silver alloy target material that can significantly improve the anti-sulfurization and anti-oxidation properties while also being easy to process. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a silver alloy target material and a preparation method and application thereof, wherein the silver alloy target material adopts a composite method of alloying, plastic deformation and heat treatment to control the microstructure morphology so that the silver alloy target material has excellent anti-sulfurization and anti-oxidation properties and good processing performance.
[0006] The inventive concept of the present invention is: on the one hand, a certain amount of Ce, aluminum-copper (Al-Cu) alloy and manganese-copper (Mn-Cu) alloy are added to Ag for microalloying; on the other hand, the microstructure morphology is regulated by combining the forging and rolling heat treatment in the preparation process. Ultimately, the anti-sulfurization and anti-oxidation properties are greatly improved without reducing the reflectivity, and the material has a higher hardness and is easy to process.
[0007] To solve the above technical problems, the first aspect of the present invention provides a silver alloy target, whose raw material components include, by weight percentage: Ag 99.25-99.93%, Ce 0.05-0.55%, aluminum-copper alloy 0.01-0.05%, and manganese-copper alloy 0.01-0.15%.
[0008] Specifically, the present invention adds a certain amount of Ce, Al-Cu alloy and Mn-Cu alloy to the silver matrix, and the elements interact with each other to effectively improve the anti-sulfurization and anti-oxidation properties of the silver alloy target. Among them: Ce has a good anti-sulfurization effect, and its mechanism of action is: the electrode potential of Ce is between 1.44-1.60V, which is higher than the electrode potential of Ag 0.799V, so adding a trace amount of Ce can improve the electrode potential of the Ag alloy target; and the sulfidation reaction belongs to the general electrochemical corrosion, and it is obvious that the increase in electrode potential will inevitably lead to an increase in the anti-sulfurization effect. At the same time, Ce can be used as a deoxidizer during the smelting process, reacting preferentially with oxygen in the solid solution to form a dense protective film, reducing the solid solution oxygen absorption and improving the purity of the target material; as a low melting point element, Ce can also reduce the melting point of the alloy, improve the melt fluidity, reduce the loose shrinkage defects in the alloy, and improve the density of the alloy; adding trace Ce can refine the grains, the radius of the Ce element is larger than that of Ag, and it can form a supercooling of the composition during solidification, play a role in non-uniform heterogeneous nucleation, and effectively prevent the growth of grains; the annealed alloy element Ce can be well evenly distributed. Ce exists in the segregation at the grain boundary, and it plays a pinning role, hindering the migration of the grain boundary, thereby achieving the effect of refining the grains.
[0009] Al-Cu alloy has good anti-sulfurization performance while ensuring high reflectivity. On the one hand, Al, as one of the metals with the highest reflectivity except for precious metals, is the key to maintaining good reflectivity in the present invention; on the other hand, the electrode potential of Cu is 0.153V, which is lower than that of Ag, and Cu is also easy to generate black CuS with H2S, which protects Ag while reducing the reflectivity of silver. Therefore, the amount of Cu added should not be too much. In addition, Al-Cu alloy has a strong dendritic solidification characteristic. The addition of an appropriate amount of Ce in the present invention reduces the alloy liquidus temperature and thus inhibits the alloy dendrite tendency, refines the Al-Cu alloy structure, and promotes the uniform distribution of Al and Cu in the Ag matrix.
[0010] The addition of Mn-Cu alloy can effectively improve the oxidation resistance and anti-sulfurization performance of silver alloy target. Its mechanism of action is similar to that of Al-Cu alloy, both of which come from the increase of Cu electrode potential and its reaction with H2S. At the same time, the addition of Mn-Cu alloy can also inhibit the migration of silver elements, thereby inhibiting bulges. This is mainly because the Mn-Cu alloy is more evenly dispersed with silver and Ce during smelting, which can effectively inhibit the migration of silver elements.
[0011] Preferably, the raw material components of the silver alloy target include, by weight percentage: Ag 99.25-99.56%, Ce 0.35-0.55%, aluminum-copper alloy 0.02-0.05%, and manganese-copper alloy 0.01-0.15%.
[0012] Preferably, the purity of Ag and Ce is not less than 99.99%.
[0013] Preferably, the Ag is in a spherical shape.
[0014] Preferably, the mass ratio of aluminum to copper in the Al-Cu alloy is (1-3):1.
[0015] Preferably, the purity of the Al-Cu alloy is not less than 99.95%, and the Al-Cu alloy is in the form of a block ingot.
[0016] Preferably, the mass ratio of manganese to copper in the Mn-Cu alloy is (2.5-5):1.
[0017] Preferably, the purity of the Mn-Cu alloy is not less than 99.95%, and the form is a block ingot.
[0018] A second aspect of the present invention provides a method for preparing the above-mentioned silver alloy target, comprising the following steps:
[0019] Ag, Ce, aluminum-copper alloy and manganese-copper alloy are mixed and smelted; the smelted alloy solution is then cast into an ingot; and the silver alloy target is obtained through forging, rolling, processing and binding.
[0020] Preferably, the smelting temperature condition is: smelting at 1250-1350° C. for 4-6 hours.
[0021] Preferably, after the Ag, Ce, aluminum-copper alloy and manganese-copper alloy are mixed, a layer of charcoal is laid on the surface thereof.
[0022] Preferably, the charcoal is oak charcoal.
[0023] Preferably, the smelting is carried out under inert atmosphere conditions.
[0024] Preferably, the inert atmosphere is an argon atmosphere.
[0025] Preferably, the casting process is: pouring the smelted alloy solution into a mold, then placing an ignition agent above the alloy solution, the main component of the ignition agent being a mixture of Fe2O3, Al and Al2O3, which is used to isolate oxygen, and then cooling with water.
[0026] Preferably, before and after the forging, the step of performing a forging heat treatment on the ingot is also included, and the temperature condition of the forging heat treatment is: heat treatment at 700-750°C for 45-50 minutes.
[0027] Preferably, before and after the rolling, the method further includes a step of performing rolling heat treatment on the forged billet, and the temperature condition of the rolling heat treatment is: performing heat treatment at 500-550° C. for 1-2 hours.
[0028] The present invention realizes the regulation of the microstructure morphology of the silver alloy target material by performing forging and rolling heat treatment under specific conditions, so that the precipitated phase is distributed in a uniform manner, and while further improving the anti-sulfurization and anti-oxidation properties of the target material, the hardness of the target material is increased, thereby improving the processing performance.
[0029] A third aspect of the present invention provides an electrode, which includes the above-mentioned silver alloy target.
[0030] A fourth aspect of the present invention provides a reflective film, which includes the above-mentioned silver alloy target.
[0031] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0032] (1) The silver alloy target of the present invention contains a certain amount of Ce, Al-Cu alloy and Mn-Cu alloy. The elements interact with each other to effectively improve the anti-sulfurization and anti-oxidation properties of the silver alloy target. Among them: Ce not only has a good anti-sulfurization effect, but also helps to improve the density of the alloy and refine the grains; Al-Cu alloy can ensure a high reflectivity while having good anti-sulfurization performance, and promote the uniform distribution of Al and Cu in the Ag matrix; Mn-Cu alloy can simultaneously improve the anti-oxidation and anti-sulfurization properties of the silver alloy target and inhibit the migration of silver elements.
[0033] (2) When preparing the silver alloy target material of the present invention, the microstructure morphology is regulated by forging and rolling heat treatment, which further improves the anti-sulfurization and anti-oxidation properties of the target material and increases the hardness of the target material, thereby improving the processing performance. The time for the prepared silver alloy target material to start blackening and sulfurization is 8.0-11.2 hours, the time for starting blackening and oxidation is 7.5-10.6 hours, and the Vickers hardness is 97-138. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The microstructure diagram of the silver alloy target prepared in Comparative Examples 1-3 and Examples 1-9;
[0035] Figure 2 The grain size diagram of the silver alloy targets prepared in Comparative Examples 1-3 and Examples 1-9;
[0036] Figure 3 The resistivity diagram of the silver alloy targets prepared in Comparative Examples 1-3 and Examples 1-9;
[0037] Figure 4 The Vickers hardness diagram of the silver alloy targets prepared in Comparative Examples 1-3 and Examples 1-9. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0039] Example 1
[0040] A silver alloy target material, the raw material components of which are calculated by weight percentage: Ag 99.85%, Ce 0.05%, Al-Cu alloy 0.05%, and manganese-copper alloy 0.05%. Among them: the purity of Ag is not less than 99.99%, and the shape is spherical; the purity of Ce is not less than 99.99%, and the purity of Al-Cu alloy (the mass ratio of aluminum to copper is 3:1) and Mn-Cu alloy (the mass ratio of manganese to copper is 5:1) is not less than 99.95%, and the shape is block ingot.
[0041] A method for preparing a silver alloy target comprises the following steps:
[0042] (1) Melting: Ag, Ce, Al-Cu alloy and Mn-Cu alloy were weighed according to weight percentage, put into a melting crucible, heated to 1320°C and maintained for 4.5 hours; Ar gas was introduced for 45 minutes; the temperature was lowered to 1260°C, oak charcoal was added and maintained for 30 minutes;
[0043] (2) Casting: Apply a release agent to the inner wall of the mold, then pour the smelted alloy solution into the mold, place an ignition agent on the top of the alloy solution, the main components of the ignition agent are a mixture of Fe2O3, Al and Al2O3, to isolate oxygen; after the ignition agent is completely burned, take the alloy ingot out of the mold; cool it with water to obtain an ingot;
[0044] (3) Forging: The ingot was heat treated before and after forging at a temperature of 720°C for 50 minutes;
[0045] (4) Rolling: The forged billet was heat treated before and after rolling at a temperature of 550°C for 1 hour;
[0046] (5) Processing: The rolled blank is processed into a circular target sample with a diameter of 80 mm and a thickness of 6 mm by wire cutting and grinding;
[0047] (6) Binding: Place the copper back plate and the circular target sample on a heating platform and keep them at 220°C for 5 hours. After keeping warm, apply liquid In to the copper back plate and the sample surface. After applying it evenly, bond the sample to the copper back plate to obtain the silver alloy target of this embodiment.
[0048] Embodiment 2-9
[0049] Referring to the components of the silver alloy target in Example 1, the difference between Examples 2-9 and Example 1 is only that the amounts of the raw materials of the silver alloy target are changed, as shown in Table 1.
[0050] Table 1:
[0051]
[0052]
[0053] Comparative Examples 1-3
[0054] Referring to the components of the silver alloy target in Example 1, the difference between Comparative Examples 1-3 and Example 1 is only that the types and amounts of the raw materials of the silver alloy target are changed, as shown in Table 2.
[0055] Table 2:
[0056]
[0057] Performance Testing
[0058] 1. Microstructure
[0059] The silver alloy targets prepared in Examples 1-9 and Comparative Examples 1-3 were cut into 10 mm × 10 mm × 5 mm samples, and then polished and etched with 400#-7000# sandpaper. The target tissue morphology was observed under an optical microscope at 1000 times magnification. The microscopic results are as follows: Figure 1 As shown, the grain size is Figure 2 shown.
[0060] Figure 1 Figures (a)-(I) correspond to the silver alloy targets prepared in Comparative Examples 1-3 and Examples 1-9, respectively. Figure 1 It can be seen that in each comparative example and embodiment, there is no significant difference in the microstructure morphology. It can be seen that compared with the traditional addition of In, the introduction of Ce, Al-Cu alloy and Mn-Cu alloy does not produce significant changes in the microstructure.
[0061] Figure 2 D1-D3 in the figure correspond to the silver alloy targets prepared in Comparative Examples 1-3, respectively, and S1-S9 correspond to the silver alloy targets prepared in Examples 1-9, respectively. Figure 2It can be seen that the silver alloy targets prepared in the comparative examples and embodiments have large differences in grain size. Compared with the addition of In, the grains are finer after adding Ce, Al-Cu alloy and Mn-Cu alloy, which has obvious advantages in improving the sputtering rate at the target application end. In addition, the small and uniform grain size will also make the film thickness more uniform during film deposition, greatly improve the film quality, and is more beneficial to improving the overall sulfurization and oxidation performance.
[0062] 2. Resistivity
[0063] The silver alloy targets prepared in Examples 1-9 and Comparative Examples 1-3 that passed the binding test were placed on a flat marble platform, and a resistivity test was performed using a four-probe resistivity meter. Each position was tested 3 times, and the average of the 3 times was taken as the final measurement result. The results are as follows: Figure 3 shown.
[0064] Figure 3 D1-D3 in the table correspond to the silver alloy targets prepared in comparative examples 1-3, and S1-S9 correspond to the silver alloy targets prepared in examples 1-9. Figure 3 It can be seen that in each comparative example and embodiment, the resistivity changes with the change of the Ag content and shows a positive correlation with the content. This is mainly because the resistivity of Ag is extremely low compared with Cu, Al, Mn and their alloys, and the Ag content in the present invention accounts for more than 99wt%, so the overall resistivity of the target material is determined by the Ag content.
[0065] 3. Hardness
[0066] The hardness of the silver alloy targets prepared in Examples 1-9 and Comparative Examples 1-3 was tested using a MH-3 microhardness tester. Each position was measured 5 times, and the average value was taken as the final measurement result. The results are shown in FIG. Figure 4 shown.
[0067] Figure 4 D1-D3 in the figure correspond to the silver alloy targets prepared in Comparative Examples 1-3, respectively, and S1-S9 correspond to the silver alloy targets prepared in Examples 1-9, respectively. Figure 4 It can be seen that the hardness of Examples 1-9 is higher than that of Comparative Examples 1-3. The main reason for this is the different grain sizes of the target materials. According to the Hall-Petch of hardness, the grain size is inversely proportional to the hardness. Therefore, in general, the smaller the grain size, the greater the hardness, which is also beneficial for later processing.
[0068] 4. Anti-sulfurization and anti-oxidation properties
[0069] The coating test was carried out on the cleaned glass substrate (glass plate size 100 mm×300 mm), with a gas pressure of 0.5 Pa, Ar gas environment, and a sputtering power of 200 W. The results are shown in Table 3.
[0070] Anti-sulfurization performance test: Under the conditions of temperature 85℃ and humidity 85%, place the coated silver alloy film in a closed chamber with H2S, observe the silver alloy film, and record the time when it starts to turn black and the final state of the film.
[0071] Antioxidation performance test: Under the conditions of temperature 85℃ and humidity 85%, place the coated silver alloy film in a closed chamber with O2, observe the silver alloy film, and record the time when it starts to turn black and the final state of the film.
[0072] Table 3:
[0073]
[0074]
[0075] As can be seen from Table 3, the silver alloy targets prepared in Examples 1-9, due to the addition of Ce, Al-Cu alloy, and Mn-Cu alloy to Ag, have better improvement effects on anti-sulfurization and oxidation performance than the silver alloy targets in Comparative Examples 1-3 with only In added. The main reason is that Ce, Al-Cu alloy, and Mn-Cu alloy can synergistically improve the electrode potential of Ag, and react with S and O before Ag, thus achieving better anti-sulfurization and oxidation effects.
[0076] Comparing Comparative Examples 1-3 with Examples 2 and 7, it can be seen that when the amount of Al-Cu alloy and Mn-Cu alloy is kept at 0.05, the anti-sulfurization and oxidation performance are greatly improved by increasing the content of Ce on the basis of removing In, and the anti-sulfurization and oxidation performance are respectively improved from 7.5 hours and 7.2 hours in Comparative Example 3 to 8.1 hours and 7.2 hours in Comparative Example 1 and 10.2 hours and 9.5 hours in Comparative Example 7. It is proved that the addition of Ce has a better anti-sulfurization and oxidation effect on Ag, and can be used as a potential favorable element for optimizing performance.
[0077] By comparing comparative examples 1-4 with comparative examples 6-9, it can be seen that when Ce, Al-Cu alloy and Mn-Cu alloy are added together, the anti-sulfurization and oxidation effects of Ag increase with the increase of Ce content, and when the Ce content is 0.55wt%, the anti-oxidation and sulfurization effects reach the best, which are 11.2 hours and 10.6 hours respectively.
[0078] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A silver alloy target, characterized in that: The raw material components include, by weight percentage: Ag 99.25-99.93%, Ce 0.05-0.55%, aluminum-copper alloy 0.01-0.05%, and manganese-copper alloy 0.01-0.15%.
2. The silver alloy target according to claim 1, characterized in that The raw material components include, by weight percentage: Ag 99.25-99.56%, Ce 0.35-0.55%, aluminum-copper alloy 0.02-0.05%, and manganese-copper alloy 0.01-0.15%.
3. The silver alloy target according to claim 1, characterized in that The purity of Ag and Ce is not less than 99.99%.
4. The silver alloy target according to claim 1, characterized in that The mass ratio of aluminum to copper in the aluminum-copper alloy is (1-3):1; and / or the mass ratio of manganese to copper in the manganese-copper alloy is (2.5-5):
1.
5. A method for preparing a silver alloy target as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Ag, Ce, aluminum-copper alloy and manganese-copper alloy are mixed and smelted; the smelted alloy solution is then cast into an ingot; and the silver alloy target is obtained through forging, rolling, processing and binding.
6. The method for preparing a silver alloy target according to claim 5, characterized in that: The smelting temperature condition is: smelting at 1250-1350° C. for 4-6 hours.
7. The method for preparing a silver alloy target according to claim 5, characterized in that: Before and after the forging, the step of performing a forging heat treatment on the ingot is also included, and the temperature condition of the forging heat treatment is: performing a heat treatment at 700-750° C. for 45-50 minutes.
8. The method for preparing a silver alloy target according to claim 5, characterized in that: Before and after the rolling, the forged billet is subjected to rolling heat treatment. The temperature condition of the rolling heat treatment is: heat treatment at 500-550° C. for 1-2 hours.
9. An electrode, characterized in that: The electrode comprises the silver alloy target material as described in any one of claims 1-4.
10. A reflective film, characterized in that: The reflective film comprises the silver alloy target material as described in any one of claims 1-4.
Citation Information
Patent Citations
Ag-based alloy sputtering target
CN101376963A
Silver-based alloy target material blank for vacuum magnetron sputtering and preparation method as well as application thereof
CN106947879A
Rolling annealing control process for silver alloy target grain homogenization
CN117187722A
Ag alloy film for electronic parts, and sputtering target for depositing ag alloy film
JP2003089830A
Electrode used in display device or input device, and sputtering target for use in electrode formation
TW201426831A
Cited By
Ultra-fine grain silver-copper alloy containing nano precipitated phase and preparation method and application of ultra-fine grain silver-copper alloy
CN120425189A